2016
DOI: 10.7197/cmj.v38i1.5000165142
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and antiangiogenic effects of methanol extracts of Lonicera caprifolium L. on C6 rat glioma cells

Abstract: SUMMARYObjective: Gliomas are brain tumors with high morbidity and mortality. For the treatment of gliomas, it is important to develop new and powerful treatments that could complement existing clinical treatment. Lonicera caprifolium L. (L. caprifolium) has various uses in herbal traditional medicine. This study was conducted to determine the phenolic acid levels and DNA damage protection potential of L. caprifolium extract, and to explore the antitumor effect of the extract by investigating its toxicity on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…Turgut et al [86] reported that gallic, protocatechuic, p-hydroxybenzoic, vanillic, caffeic, chlorogenic, syringic, p-coumaric, ferulic, o-coumaric, rosmarinic, and trans-cinnamic acids are the phenolic acids found in L. caprifolium. Phenolic acids such as benzoic acid, cinnamic acid, vanillic acid, salicylic acid, p-hydroxybenzoic acid (p-HBA), and tetradecanoic acid were isolated and identified from P. cablin by Wu et al [87].…”
Section: Discussionmentioning
confidence: 99%
“…Turgut et al [86] reported that gallic, protocatechuic, p-hydroxybenzoic, vanillic, caffeic, chlorogenic, syringic, p-coumaric, ferulic, o-coumaric, rosmarinic, and trans-cinnamic acids are the phenolic acids found in L. caprifolium. Phenolic acids such as benzoic acid, cinnamic acid, vanillic acid, salicylic acid, p-hydroxybenzoic acid (p-HBA), and tetradecanoic acid were isolated and identified from P. cablin by Wu et al [87].…”
Section: Discussionmentioning
confidence: 99%
“…Эфирное масло этого вида, придающее цветкам душистый запах, можно использовать в ароматерапии (Ilieş et al, 2014). Установлено противораковое и антиангиогенное действие экстрактов из L. caprifolium (Turgut et al, 2016). Последние публикации показывают перспективы использования эфирного масла этого вида, содержащего в составе еще и пачулевый спирт, в качестве инсектицида и/или репеллента против разных видов москитов, преимущественно против комаров (Muturi et al, 2019).…”
Section: Introductionunclassified